2013
DOI: 10.1177/0883073812474692
|View full text |Cite
|
Sign up to set email alerts
|

Severe Neurologic Involvement of Degos Disease in a Pediatric Patient

Abstract: A 14-year-old male presented with paresthesias on the right upper and lower extremities, headache, and vomiting. In addition to worsening paresthesia and weakness on the right side of his body, blurred vision, fever, and skin lesions developed. He also had skin lesions characterized with 3-10 mm papules with a white atrophic center surrounded by pink rim mostly on the trunk and lower extremities. Brain magnetic resonance imaging showed chronic subdural effusion and encephalomalacia of the left cerebral hemisph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 13 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…In patients with extracutaneous involvement (n = 43, excluding six patients whose information was not available and three patients with cutaneous involvement after systemic manifestations). [6][7][8] Moreover, we found that in patients in the systemic category, the first systemic manifestation occurred at a median of 2.0 years (95% CI, 0-7.8) after disease onset. The gastrointestinal tract and CNS were involved in 43 of 52 (82.7%) and seven of 22 patients (42.3%), respectively, of whom 30 (69.8%) and 12 patients (54.5%) died during follow up.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In patients with extracutaneous involvement (n = 43, excluding six patients whose information was not available and three patients with cutaneous involvement after systemic manifestations). [6][7][8] Moreover, we found that in patients in the systemic category, the first systemic manifestation occurred at a median of 2.0 years (95% CI, 0-7.8) after disease onset. The gastrointestinal tract and CNS were involved in 43 of 52 (82.7%) and seven of 22 patients (42.3%), respectively, of whom 30 (69.8%) and 12 patients (54.5%) died during follow up.…”
Section: Discussionmentioning
confidence: 71%
“…The mortality in all patients with the systemic type was 65.3% (34/52), whereas no patient death was observed among the 28 patients with pure cutaneous involvement ( P < 0.05). In patients with extracutaneous involvement ( n = 43, excluding six patients whose information was not available and three patients with cutaneous involvement after systemic manifestations) . Moreover, we found that in patients in the systemic category, the first systemic manifestation occurred at a median of 2.0 years (95% CI, 0–7.8) after disease onset.…”
Section: Discussionmentioning
confidence: 78%
“…Although DD most commonly affects middle-aged Caucasian adults, with a male preponderance, onset from birth to 70 years has been described (1,2). Pediatric cases are rare, and only a single case with presentation at birth has been reported (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(18)(19)(20)(21)(22)(23). Most cases appear to be sporadic, but some suggest the possibility of autosomal dominant inheritance (1,9,12).…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to address the presumed pathogenetic mechanism, antiplatelet or anticoagulant agents such as acetylsalicylic acid, dipyridamole, and heparin are often prescribed (2,4,6,(8)(9)(10)(11) (Table 1). Immunosuppressive regimens including cyclosporine, azathioprine, cyclophosphamide, and systemic corticosteroids have been tried and are ineffective (2,3,6,7,20,21) (Table 1). Eculizumab and treprostinil have proven beneficial in some cases, although the evidence is anecdotal (7,18).…”
Section: Discussionmentioning
confidence: 99%
“…7 There are no proven treatments for the malignant and progressive version of this condition, and in particular, there is no information on treatment of infants. Treatments that have been tested include aspirin and other antiplatelet therapies, calcium channel blockers, steroids, and other immunosuppressive medications, 8 and there is limited reported success in single cases in adulthood with the complement inhibitor eculizumab and the prostacyclin analogue treprostinil. 9,10 As our case illustrates, this condition can have a devastating and fatal outcome.…”
mentioning
confidence: 99%